2005
DOI: 10.1016/j.ydbio.2005.08.041
|View full text |Cite
|
Sign up to set email alerts
|

The right ventricle, outflow tract, and ventricular septum comprise a restricted expression domain within the secondary/anterior heart field

Abstract: The vertebrate heart arises from the fusion of bilateral regions of anterior mesoderm to form a linear heart tube. Recent studies in mouse and chick have demonstrated that a second cardiac progenitor population, known as the anterior or secondary heart field, is progressively added to the heart at the time of cardiac looping. While it is clear that this second field contributes to the myocardium, its precise boundaries, other lineages derived from this population, and its contributions to the postnatal heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
530
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(553 citation statements)
references
References 53 publications
23
530
0
Order By: Relevance
“…SHF lineage tracing with ROSA26 mT/mG 24 mice showed that a subset of endothelial cells within the aorta and aortic valves were derived from the SHF (Figure 5G and 5H). SHF‐derived endothelial cells are also known to populate the pulmonary trunk and pulmonary valve, suggesting that the effect of Notch1 may still be limited to the endothelial cell layer 22. Because other publications have implicated the role of neural crest cells in OFT formation, we obtained neural crest–specific Wnt1‐Cre mice to ascertain the role of Notch1 specifically in the neural crest 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHF lineage tracing with ROSA26 mT/mG 24 mice showed that a subset of endothelial cells within the aorta and aortic valves were derived from the SHF (Figure 5G and 5H). SHF‐derived endothelial cells are also known to populate the pulmonary trunk and pulmonary valve, suggesting that the effect of Notch1 may still be limited to the endothelial cell layer 22. Because other publications have implicated the role of neural crest cells in OFT formation, we obtained neural crest–specific Wnt1‐Cre mice to ascertain the role of Notch1 specifically in the neural crest 23.…”
Section: Resultsmentioning
confidence: 99%
“…Nos3 −/− and Notch1 +/− ;Nos3 +/− mice were bred to obtain Notch1 +/− ;Nos3 −/− mice (n=49) and littermate controls (n=216) and were genotyped, as described previously 20. For lineage‐specific deletions of Notch1 (using Tie2‐Cre,21 Mef2C‐Cre,22 Wnt1‐Cre23), Nos3 −/− ;Cre +/− male mice were bred with Notch1 flox/wt ;Nos3 +/− female mice to obtain Notch1 flox/wt ;Tie2‐Cre +/− ;Nos3 −/− (n=6) mice, Notch1 flox/wt ;Mef2C‐Cre +/− ;Nos3 −/− (n=7), Notch1 flox/wt ;Wnt1‐Cre +/− ;Nos3 −/− (n=4), and control littermates (n=4, n=4, n=4, respectively). SHF lineage tracing was completed by breeding Mef2C‐Cre +/− male mice with ROSA26 mT/mG female mice 24…”
Section: Methodsmentioning
confidence: 99%
“…As previously shown, part of the cause is failure of the AHF-derived RV to form . This is not from failure of the AHF to contribute to the heart, but rather from problems in differentiation (Verzi et al, 2005). The role of MEF2C in AHF differentiation is beginning to be defined through promoter and mutant analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the AHF is transcriptionally distinct from the posterior cells of the SHF in that promoter elements of the mef2c and nkx2.5 genes are active in the AHF but not the posterior region (Dodou et al, 2004;Takeuchi et al, 2005). Lineage tracing experiments using the AHF regulatory elements from the mef2c gene show that the outflow tract (OFT), right ventricle (RV), and ventricular septum are AHF derivatives (Verzi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation